Influence of Foliar Application of NAA, Zinc Sulphate and Calcium Nitrate on Flowering, Yield and Quality Attributes of Winter Season Guava - Pal, Shalini; Tripathi, V. K.; Awasthi, Manuj (International Journal of Bio-resource and Stress Management, 2026)
The present experiment was conducted from June to December, 2024 at Guava Orchard, Department of Fruit Science, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, U.P., India. This study aimed to improve the fruiting attributes, physical attributes, fruit yield, and quality of the L-49 cultivar of guava. The experiment was laid out in RBD with three replicates of each treatment. Total 10 treatments including one control, viz., NAA at 25 ppm, NAA at 50 ppm, NAA at 75 ppm, ZnSO4 at 0.50%, ZnSO4 at 0.50 %, ZnSO4 at 0.75%, ZnSO4 at 1.0%, Calcium nitrate at 0.50%, Calcium nitrate at 1.0%, Calcium nitrate at 1.50%, and Control, i.e. water spray. The present investigation, it was reported that the application of ZnSO4 at 1.0% with significantly increased flowers (59.60) shoot-1, fruit set (59.73%), and decreased fruit drop (41.67%), increased fruit retention (58.33%), fruit weight (152.40 g), fruit length (7.68 cm), fruit width (7.25 cm), fruit volume (156.84 cc), specific gravity (1.19 g cc-1), and fruit yield (56.84 kg) plant-1, pulp (96.56%), pulp: seed ratio (28.14) and minimum number of seeds (253) fruit-1 and seed weight (5.23 g) fruit-1 and quality parameters like: TSS (12.09°Brix), total sugars (8.02%), reducing sugars (3.84%), non-reducing sugars (4.18%), and decreased titratable acidity (0.43%) content. Hence, plants treated with ZnSO4 at 1.0% could also be used to improve fruiting, overall yield, and quality characteristics of the L-49 cultivar of guava.